2020
DOI: 10.1159/000508810
|View full text |Cite
|
Sign up to set email alerts
|

Similarities, Differences, and Potential Synergies in the Mechanism of Action of Albumin Dialysis Using the MARS Albumin Dialysis Device and the CytoSorb Hemoperfusion Device in the Treatment of Liver Failure

Abstract: <b><i>Introduction:</i></b> Liver failure is characterized by compromised hepatic detoxification, protein synthesis, and metabolic derangements leading to an accumulation of a broad spectrum of water-soluble and lipophilic toxins as well as immune system mediators. Exploring complex detoxification mechanisms to therapeutically target those components, this article will focus on similarities, differences, and potential synergies in the mechanism of albumin dialysis and hemoperfusion. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…The mean age in our study group was 34 ± 14 years. The median number of organ dysfunctions was 3 [2][3][4][5][6] with 75% of patients having grade III or IV hepatic encephalopathy. The mean SOFA score before the start of CRRT was 12.0 ± 2.1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age in our study group was 34 ± 14 years. The median number of organ dysfunctions was 3 [2][3][4][5][6] with 75% of patients having grade III or IV hepatic encephalopathy. The mean SOFA score before the start of CRRT was 12.0 ± 2.1.…”
Section: Resultsmentioning
confidence: 99%
“…2 The use of haemoadsorption has recently been introduced in clinical practice for managing inflammation in different clinical scenarios including sepsis, cardiac surgery or acute pancreatitis. 3,4 The theoretical benefits in this extracorporeal therapy in ALF has been tested in two experimental studies that have demonstrated an improvement of both liver functional tests and near complete removal of proinflammatory cytokines 5,6 but these results need further assessment in clinical trials. To date, only a few clinical cases have been published showing the potential clinical benefits of haemoadsorption in liver failure 7,8 showing an improvement in biochemical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Other blood purification methods, such as CytoSorb ™ therapy, also seem promising [59,60], but they have not yet been evaluated in a randomized setting. Nevertheless, according to a recent in vitro experimental model, Cyto-Sorb hemoperfusion leads to an initially faster removal of cytokines, like TNF-α and IL-6, as well as more effective reduction of albumin-bound toxins, such as indirect bilirubin and bile acids, compared to MARS [61].…”
Section: Discussionmentioning
confidence: 99%
“…Acute forms of liver dysfunction and failure also share the pathophysiological features of dysregulated inflammatory response with sepsis, which serves as the basis of the rationale hemoadsorption in liver dysfunction [ 12 , 13 , 14 ]. There are some case reports, case series, and in vitro data indicating effective removal of bilirubin, bile acids, and ammonia from the blood by using hemoadsorption [ 15 , 16 , 17 , 18 ]. In a recent in vitro study, CytoSorb was also found superior to albumin dialysis (Molecular Adsorbent Recirculating System: MARS) as far as bilirubin, bile acid, ammonia, and cytokine removal are concerned [ 17 ].…”
Section: Introductionmentioning
confidence: 99%